The Fading History of Trevor Owen: A Figure of Jamaica's Independence Fashion Industry. (3rd April 2018) - Gregory, Joy
Abstract: In this article, the photographic artist Joy Gregory reflects on the discovery of the uncataloged archives of couturier Trevor Owen and the 2013 Artists' Residency that took place at the Beach House, Owen's home and atelier in Reading, Jamaica. In 2005, five miles down the coast from Montego Bay, Derek Bishton and his wife Merrise purchased a small beach house retreat in Reading. They discovered among the things left in the property, a store room filled with dressmaking materials: row upon row of stiff patterns hanging from the ceiling, bundles of material, boxes of buttons, and numerous jars of odds and ends, along with several portfolios of designs, newspaper clippings, address books, and notebooks with measurements of former clients. The story of Owen's 30-year career, the societies in which he moved, the company that he kept and his occupation of a property that was once part of the Tate & Lyle sugar plantation, also unravels the story of Jamaica's colonial past, that is, the uneven relationship between the island and Europe. Absent from European and American fashion histories, Owen is recognized in Jamaica as the couturier who dressed wealthy local residents and tourists from Kingston, the wider Caribbean, the USA, and Europe, jet-setters who populated the Montego Bay strip in its hey-day during the 1950s. He is a major figure in Jamaica's post-Independence fashion industry. This timely article, illustrated primarily by Gregory's photographs, highlights and responds to his legacy.